2014
DOI: 10.1007/s11999-013-3124-2
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet Use During Cementation Only During Total Knee Arthroplasty: A Randomized Trial

Abstract: Background Total knee arthroplasty with the use of a tourniquet during the entire operation has not been shown to improve the performance of the operation and may increase the risk of complications. Questions/purposes We asked whether the limited use of a tourniquet for cementation only would affect (1) surgical time; (2) postoperative pain and motion of the knee; (3) blood loss; or (4) complications such as risk of nerve injuries, quadriceps dysfunction, and drainage compared with use of a tourniquet througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 22 publications
(53 reference statements)
1
57
2
1
Order By: Relevance
“…No differences between the groups regarding the translation or rotation of the components as measured by RSA Tarwala et al [26] Randomized trial. To use a tourniquet only during cementation or up to wound closure…”
Section: Ref Type Of Study Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…No differences between the groups regarding the translation or rotation of the components as measured by RSA Tarwala et al [26] Randomized trial. To use a tourniquet only during cementation or up to wound closure…”
Section: Ref Type Of Study Outcomementioning
confidence: 99%
“…Besides, patients with a tourniquet did not have neither a higher risk of thromboembolic complications nor significant difference in the time of surgery compared with patients without a tourniquet [25] . Also, in 2013, Tarwala et al [26] in a randomized trial, examined the outcomes of the use of a tourniquet only during cementation and found that it offered bloodless bone for fixation, and did not influence the surgical time, pain, range of knee motion and total blood loss. Consequently, they recommended this method, claiming that it may restrict the possible risks related to prolonged tourniquet use [26] .…”
Section: Cpm: To Use or Not To Use?mentioning
confidence: 99%
See 1 more Smart Citation
“…Ejaz et al [19] also reported the same finding. However, Liu et al [14] and Tarwala et al [20] found that although patients who were treated with tourniquet had better muscular function and shorter hospital stay, their twelve-month ROM was not significantly different from that of patients who underwent tourniquet-assisted surgery. On the other hand, electromyographic alterations in the quadriceps muscle were also reported after using tourniquet for knee surgeries [10].…”
Section: Introductionmentioning
confidence: 96%
“…To the editor, We read the Level I study by Tarwala and colleagues [11] with great interest. The study compared the operative tourniquet group to cementation tourniquet group in patients undergoing TKA.…”
mentioning
confidence: 99%